SNAP: Fault tolerant event location estimation in sensor networks using binary data - Panayiotou, Christos G.; Michaelides, Michalis P. (My University, 2009)
This paper investigates the use of wireless sensor networks for estimating the location of an event that emits a signal that propagates over a large region. In this context, we assume that the sensors make binary observations and report the event (positive observations) if the measured signal at their location is above a threshold; otherwise, they remain silent (negative observations). Based on the sensor binary beliefs, a likelihood matrix is constructed whose maximum value points to the event location. The main contribution of this work is Subtract on Negative Add on Positive (SNAP), an estimation algorithm that provides an efficient way of constructing the likelihood matrix by simply adding \pm 1 contributions from the sensor nodes depending on their alarm state (positive or negative). This simple estimation procedure provides very accurate results and turns out to be fault tolerant even when a large percentage of the sensor nodes report erroneous observations. © 2009 IEEE.
Keywords: Maximum likelihood estimation; Fault tolerance; Fault tolerant systems; Wireless sensor networks; Estimation; Probability density function; Noise